Social Media Influence on Civic Engagement Among Young Filipinos - Joemelyn Mesajon; Cristamae Canciller; Rommel Gregorio; Mary Ann Alampay (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2025)
This study examines the influence of social media use on civic engagement and political awareness among young Filipinos in the digital era. Using a mixed-method approach combining survey data (n = 200) and in-depth interviews, the research analyzes the relationship between platform usage intensity, user motivation, and the level of youth participation in social and political activities. The findings reveal that the majority of Filipino youth use Facebook and TikTok for more than three hours per day, with entertainment (60%) as the primary motivation, followed by social information (25%) and political participation (15%). A moderate positive correlation (r ≈ 0.45, p < 0.01) is found between social media use and civic engagement, indicating that higher online activity is generally associated with increased social awareness and participation. TikTok is more effective in raising awareness of social issues, while Facebook facilitates coordination of offline civic actions such as community projects and volunteer activities. However, the persistence of slacktivism and low trust in political institutions remain significant barriers that prevent digital engagement from translating into concrete action. The study underscores the potential of social media as a tool for civic education and democratic participation while highlighting the need for programs that link digital engagement to real-world civic involvement. These findings provide both academic and practical insights into enhancing youth participation in the Philippines’ evolving digital democracy.